The Effectiveness of Madrasah Head Leadership Competency in Increasing Educational Quality in Madrasah Tsanawiyah Private Vocational School, Al Manar Medan - Chairoel Idris; Mesiono (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2019)
This research aims to explain: (1) the competence of leadership of MTs Al Manar Medan Head Master; (2) the quality of education MTs Al Manar medan; (3) the effectiveness of leadership’s competence of MTs Al Manar Medan Head Master in improving the quality of education in MTs Al Manar Medan. This research was conducted by using qualitative descriptive approach. Research Subject is Head Master. The informants are Head Master, Vice of Head Master and Teachers. The data collection technique in this research is by: (1) Observation, (2) Interview, and (3) Documentation Study. Data Analysis Process is done by: Data Reduction, Display Data and Conclusion Drawing/Verification. The collected data is examined the validity of data by using Triangulation Data. The results of this research are: (1) Head Master’s Leadership Competence of MTs Al Manar Medan include; (a) Personality Competencies, (b) Managerial Competencies, (c) Supervision Competencies, and (d) Social Competencies. (2) Quality of Education in MTs Al Manar Medan, Teachers are able to carry out the learning process well in accordance with the RPP that has been developed in accordance with the needs of schools, mastery of good learning media by teachers, discipline teachers and good students, students are able to follow the competitions in outside the school, the quality of graduates can compete with elite schools in Medan City. (3) The effectiveness of Headmaster Leadership Competence in Improving the Quality of Education includes: (a) Personality Competence, Head Master able to give good characters to teachers and students. (b) Managerial Competence, Head master able to makes annual program well, guide teachers and education personnel in performing tasks, motivate teachers to improve teacher professionalism, and maximize school’s facilities and infrastructure. (c) Supervision Competencies, Head master evaluates the performance of teachers and education personnel on a regular basis at the end of every end years of learning, principals provide direct supervision during the learning process in the classroom. (d) Social Competence, headmaster participate in any activity within and outside the school.